COLORED LIGHT-TO-VOLTAGE CONVERTERS BASED ABSORBANCE METER - Pereira, M.; Postolache, O.; Girao, P.; Ramos, Helena (International Journal of Computing, 2014)
A low-cost absorbance meter for dissolved compounds identification and concentration evaluation is proposed. The main elements of the system are a white light source and a set of three colored light-to-voltage converters. The system includes auto-calibration capabilities and compensates spectral sensitivity variation of the optical source and detectors. A neural network-processing scheme is used to identify dissolved compounds and evaluate the correspondent concentrations.